2013
DOI: 10.1128/genomea.00683-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Streptococcus equi subsp. zooepidemicus Strain S31A1, Isolated from Equine Infectious Endometritis

Abstract: We present the draft genome sequence of Streptococcus equi subsp. zooepidemicus S31A1, a strain isolated from equine infectious endometritis in Denmark. Comparative analyses of this genome were done with four published reference genomes: S. zooepidemicus strains MGCS10565, ATCC 35246, and H70 and S. equi subsp. equi strain 4047.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Previous studies have indicated that the M protein is triggering this uptake mechanism, and in S. pyogenes serotype M1, the M protein acts as a primary invasin (Cue et al, 1998 ). M-like proteins have been found in S. zooepidemicus and we have identified M-like proteins in the strains investigated in this study as well (Da Piedade et al, 2013 ; unpublished genome assemply of strain 1-4a). These proteins could be involved in the triggering of membrane ruffling, but further specific studies would be needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Previous studies have indicated that the M protein is triggering this uptake mechanism, and in S. pyogenes serotype M1, the M protein acts as a primary invasin (Cue et al, 1998 ). M-like proteins have been found in S. zooepidemicus and we have identified M-like proteins in the strains investigated in this study as well (Da Piedade et al, 2013 ; unpublished genome assemply of strain 1-4a). These proteins could be involved in the triggering of membrane ruffling, but further specific studies would be needed to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 70%
“…The mechanism of uptake into host cell caveolae has been linked to the binding of fibronectin to the streptococcal FnBPs and the subsequent binding to the host cell α5β1 integrins leading to integrin clustering and caveolae aggregation, which results in the forming of the large invaginations in the host cell membrane without accumulation of actin (Rohde et al, 2003 ). It can thus be speculated that the FnBPs found in the S. zooepidemicus strains investigated in this study could trigger this uptake mechanism (Da Piedade et al, 2013 ; unpublished genome assemply of strain 1-4a), even though differences in the sequence of the FnBPs between streptococcal species can lead to different uptake mechanisms (Rohde et al, 2011 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, some strains of S. equi subsp. zooepidemicus, regarded as an opportunistic pathogen in humans as well as horses (19), express an SFS-like protein with only one FN-binding repeat (21,22). SFS with a single repeat is predicted to have only the loose monovalent, single-step binding to FN and not to form a stable complex with FN.…”
Section: Discussionmentioning
confidence: 99%